Kinetics and Adsorption of Molecularly Imprinted Polymers Dibutylphthalate - Fauziah, St; Sullahi, Fausan; Soekamto, Nunuk; Taba, Paulina (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2022)
Molecularly Imprinted Polymers (MIP) are polymers with active sites that can recognize target molecules selectively. This study aims to determine the kinetics and adsorption capacity of MIP_DBP. The method used in the synthesis of MIP_DBP was precipitation polymerization using methacrylic acid (MAA) monomer, Ethyleneglycol Dimethacrylate (EGDMA) cross linker, DBP as a template molecule, and toluene as a solvent. The MIP_DBP obtained is a white solid. The results of the MIP_DBP adsorption kinetics test followed the pseudo-second-order kinetics model and the adsorption capacity according to the Freundlich isothermal adsorption model with the adsorption capacity value for DBP was 9.38 mg/g.